Public as Practice - Boomgaard, Jeroen (Socialmedicinsk tidskrift, 2019)
"Public" is a huge concept in current debates on culture, yet the notion itself remains largely unexamined and unexplored, particularly as it applies to culture and the arts. The meanings of both "art publics" and "public space" have become complex at a time when boundaries between public and private are shifting, and "the public" actually comprises different groups of changing composition and identity. What does it mean to be public today? And what is the role of art in constituting both "public space" as well as "a public"?